A pericyclic-based approach to the total synthesis of retigeranic acid A. - Barnes, Michael Lee. (University of Ottawa (Canada), 1997)
The preparation of a key synthetic intermediate for the total synthesis of retigeranic acid A (1) through the use an intramolecular Diels-Alder reaction is described. Our approach to retigeranic acid A involved two key building blocks, a trans-hydrindane 52 and a unique tricyclic ketone 51. The building block 52 has been successfully synthesized in the Fallis laboratory, but the synthesis of 51 by an intermolecular Diels-Alder has been difficult. A new route to 51 was devised, involving the use of an intramolecular Diels-Alder reaction. The synthesis started with the preparation of the ketone ester 76 in three steps from commercially available (R)-(+)-pulegone in a 46% yield. Alkylation of 76 with the tosylate 78, followed by oxidative bond cleavage generated the diketone ester 80 in an overall yield of 44%. An intramolecular aldol-condensation and subsequent reduction produced the diol 72. A selective DCC coupling with 2-chlorocrylic acid afforded the dienophile-alcohol 71 in a yield of 46%. A variety of methods were investigated for the dehydation of the alcohol to the diene 70. In the final synthetic route, 71 was quantitatively oxidized with activated MnO$\sb2$ to the ketone 109. The kinetic enolate of 109 was trapped using collidine and triisopropylsilyltrifluoromethanesulfonate, producing the desired diene 110 as a 1:1 mixture. This unstable compound, when heated in a refluxing 10 mole % solution of hydroquinone in benzene, underwent the desired intramolecular Diels-Alder reaction to give the adduct 112 in a yield of 64%.* ftn*Please refer to the dissertation for diagrams.
Keywords: Chemistry, Organic.